Experimental Study of Hydrothermal Spallation Drilling. (February 2019) - Wang, Mingbo; Wang, Ning
Abstract: Geothermal energy has gained more and more attention from all around the globe for its cleanness and efficiency. In the meantime, wells are drilling more and more deeper to develop oil and gas resources. Low rate of penetration is the common problem faced by geothermal wells and deep oil wells. To speed up the development of geothermal energy and petroleum resources in deep formation, a hydrothermal drilling method is proposed here in this paper and the drilling mechanism along with an in-lab experimental setup have been analyzed.